Dynamics of unsteady axisymmetric of Oldroyd-B material with homogeneous-heterogeneous reactions subject to Cattaneo-Christov heat transfer - Yasir, Muhammad; Khan, Masood (Alexandria engineering journal, 2023)
In several industrial and engineering applications, the Catteno-Christov heat flux plays a major role in the flow and heat transport of non-Newtonian fluids. Therefore, the goal of this study is to investigate the characteristics of homogeneous-heterogeneous reactions in the axisymmetric flow of Oldroyd-B materials using heat conduction analysis. The heat transfer phenomenon is examined from the non-Fourier heat flux model perspective. The governing flow field equations are developed using the rheological formulation of the Oldroyd-B fluid model, which is transformed into a set of nonlinear differential equations by utilizing the proper similarity conversions. The series solutions for the velocity, thermal, and solutal distribution are derived. The physical behaviors of relevant parameters are discussed in detail. The findings reveal that for the curvature parameter, the fluid velocity improves near the cylinder surface and no motion occurs away from the surface, while this predicts the dual behavior on temperature and concentration distributions. Further, fluid relaxation and retardation time exhibit opposite behavior on fluid velocity. Additionally, the results demonstrate that the homogeneous response parameter exhibits contradicting behavior on the concentration field while the thermal relaxation parameter lowers the temperature field.